Severe Inflammatory Bowel Disease Manifestations in a Patient with Post-Acute COVID-19 Syndrome (PACS): A Case Report and Literature Review - Riswanto, Arival Yanuar; Waskito, Langgeng Agung; Arfijanto, Muhammad Vitanata; Imro'ati, Tri Asih; Nasronudin, Nasronudin (Indonesian Journal of Tropical and Infectious Disease, 2026)
Post-acute COVID-19 syndrome (PACS) refers to the persistence or recurrence of symptoms lasting more than four weeks after the acute phase of COVID-19. Based on symptom duration, it is classified as subacute symptomatic COVID-19 or long COVID. The interaction between SARS-CoV-2 and the angiotensin-converting enzyme 2 (ACE2) receptor triggers immune system activation, cytokine production, and redistribution of immune cells. Impaired self-tolerance hampers immune reconstitution. In combination with environmental and genetic factors, this dysregulated immune response may act as a potential trigger for autoimmune disease, such as Inflammatory Bowel Disease (IBD). This article aims to describe a possible case of IBD, specifically Crohn’s disease developing as a manifestation of PACS. A 57-year-old male presented with hematemesis, nausea, and decreased appetite four weeks after recovering from COVID-19 infection. Esophagogastroduodenoscopy (EGD) was performed and the results were esophagitis, gastroduodenitis, and multiple lacerations of the gastric corpus. Colonoscopy demonstrated findings consistent with Crohn’s disease, including mucosal ulcerations and segmental inflammation. With supportive therapy and administration of 300 mg of infliximab, 500 mg of mesalazine three times daily, and 125 mg of methylprednisolone intravenously every 24 hours, the patient demonstrated clinical improvement and resolution of bleeding. This case highlights a possible association between PACS and de novo Crohn’s disease, suggesting that post-viral immune dysregulation following COVID-19 may unmask or trigger IBD in predisposed individuals. Clinicians should remain vigilant for gastrointestinal manifestations suggestive of IBD in patients with persistent digestive symptoms after COVID-19 infection, as early recognition and targeted therapy are essential for improving outcomes.